Das Verhalten landwirtschaftlicher Entscheider*innen bei der Adoption nachhaltiger Prozessinnovationen in Deutschland; The Behavior of Agricultural Decision-Makers towards the Adoption of Sustainable Process Innovations in Germany - Verena Otter; Maximilian Deutsch (German Journal of Agricultural Economics (GJAE), 2023)
– In reaction to new challenges of shifting sustainability requirements and climate change in the agricultural sector, sustainable process innovations are a way to combine food production with diverse ecosystem services. Despite their advantages, which have long been described in research, the actual adoption rates of these innovations in agricultural practice in Germany are rather low. In order to promote their wider dissemination, the question concerning the so far rarely investigated adoption factors of sustainable process innovations in agriculture is of particular importance. It is the aim of the present study to determine the affiliation of agricultural decision-makers to the different adoption stages 'precontemplation', 'contemplation', 'preparation' and 'action' of sustainable process innovations, using the example of agroforestry systems, and to illustrate the influence of various farmer and farm characteristics as adoption factors on the affiliation of farmers to those stages. Based on quantitative survey data of 209 German farmers, the transtheoretical model of behavior change is applied to the adoption of innovations using descriptive statistics, confirmatory factor analysis and ordinal regression analysis. The results show that at the currently dominating low adoption levels, farmers' attitude towards the implementation of agroforestry systems on their own farms as an adoption factor has the strongest positive influence on the adoption. While existing experiences with renewable energies also have a positive influence on the adoption, the opposite is true for previous experiences with short rotation coppice (SRC) and agroforestry systems (AFS). From a regional perspective, a higher adoption probability can be observed in southern Germany. Based on the results, the following targeted measures are developed to further disseminate innovative land use systems through improving farmers' attitude and to establish a group of pioneer farmers: Improvement of communication about requirements and potentials of innovations; stronger anchoring of sustainable process innovations in the curricula of agricultural vocational training and of study programs; establishment of permanent training and professional development offers; establishment of long-term, low-threshold subsidy programs; and regional differentiation of measures.
Keywords: 330; Agroforstsysteme; Innovationsadoption; Einstellung; nachhaltige Landnutzung; transtheoretisches Modell der Verhaltensänderung; ordinal logistische Regression